2015
DOI: 10.1208/s12249-015-0372-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Dissociation Energetics of Some Selected Ligand Drugs Bound on Human Serum Albumin by Differential Scanning Calorimetry

Abstract: Abstract. Drug-protein binding may play a role in the thermal energetics of protein denaturation and could lead to the determination of its equilibrium dissociation parameter. The aim of this study was to assess the energetics of a drug that was bound to human serum albumin (HSA) during thermal denaturation. Drugs that were bound at a single high-affinity primary binding site on HSA, including diazepam and ibuprofen, were employed. Commercial HSA was treated with charcoal to remove stabilizers and adjusted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It is known, that ligand binding gives an increment in the thermal stability of protein due only to the coupling of binding with unfolding [29]. Faroongsarng [30] studied assessment of the dissociation energies of diazepam and ibuprofen bound on HSA by DSC method and found that the denaturation of HSA incubated with the drugs was done at higher temperatures than HSA itself depending on drugs′ concentrations. Similar findings were demonstrated by other authors [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…It is known, that ligand binding gives an increment in the thermal stability of protein due only to the coupling of binding with unfolding [29]. Faroongsarng [30] studied assessment of the dissociation energies of diazepam and ibuprofen bound on HSA by DSC method and found that the denaturation of HSA incubated with the drugs was done at higher temperatures than HSA itself depending on drugs′ concentrations. Similar findings were demonstrated by other authors [31,32].…”
Section: Resultsmentioning
confidence: 99%